Effect of steam de-alumination on the interactions of propene with H-ZSM-5 zeolites. Issue 39 (17th June 2020) - Hawkins, Alexander P.; Zachariou, Andrea; Parker, Stewart F.; Collier, Paul; Barrow, Nathan; Silverwood, Ian P.; Howe, Russell F.; Lennon, David
Abstract : Inelastic and quasi-elastic neutron scattering are used to investigate how steaming changes the physico-chemical characteristics of the zeolite ZSM-5. Abstract : Steam de-alumination is used to prepare a H-ZSM-5 material representative of industrial acid zeolite catalysts. Characterisation shows extensive loss of zeolite acidity but minimal loss of framework crystallinity in the treated material. The material's interaction with propene is probed by means of inelastic and quasielastic neutron scattering, providing information on the reactivity and mobility of the propene respectively. These results are compared to those previously obtained for propene in the untreated zeolite. The steaming treatment resulted in decreased reactivity of the zeolite toward olefin oligomerization, higher temperatures for reaction initiation, and increased mobility of the propene in the zeolite at all temperatures. Analysis of the motions of the propene revealed by QENS shows the mobility to be comparable to those previously reported for propane in similar materials but occurring at slower velocities due to the greater rigidity and polarisation of the propene molecule.